ChatGPT와 회계정보: 온실가스 회계기준 적용 및 XBRL보완 가능성 탐색을 중심으로 - 윤양인(Yangin Yoon) (한국콘텐츠학회 논문지, 24(5), 2024)
인공지능은 ChatGPT 등을 중심으로 최근 그 발전 속도가 가속화되고 있으며, 다양한 분야에서의 응용사례 또한 활발히 논의되고 있다. 본 연구에서는 생성형 인공지능 언어모델을 회계분야에 적용하여 회계처리(분개생성) 능력을 중심으로 평가하였다. 새로운 회계기준을 적용하는 성능을 테스트하기 위해 특수한 분야인 온실가스 회계처리 문제를 활용하여 성능을 평가하였다. 실험결과 ChatGPT-4는 주어진 특정한 회계기준을 적절히 적용하여 회계기준에 부합하는 분개를 생성하였다. 이와 함께 회계정보의 자료교환 표준인 XBRL을 보완할 수 있는 가능성을 탐색하였다. ChatGPT-4를 활용하여 태깅이 없더라도, 문서로부터 특정한 회계정보를 추출하는 것이 가능하였다. 일부 한계점이 존재하지만 향후 활용의 가능성이 존재하며, 이러한 기능은 회계 교육에서도 학습자의 회계개념 이해 및 심화학습 목적으로도 활용할 수 있을 것이다. Generative AI models are rapidly evolving and revealing new possibilities in many areas. This study examines the performance of ChatGPT with respect to accounting issues for generating journal entries. This study uses the Korean accounting standard for carbon credits, which is a specific issue rather than a general accounting concept, to test the performance of ChatGPT. ChatGPT generates appropriate journal entries according to the given accounting standard. This study also demonstrates the potential of ChatGPT to complement XBRL tagging, which facilitates the automatic exchange of accounting data. ChatGPT identifies specific information from unstructured accounting documents. Despite some limitations, ChatGPT can be effectively employed in accounting tasks. In addition, the AI model can be used for accounting education to deepen the understanding of accounting concepts. KCI Citation Count: 0